Sengketa Tanah Kavling di Kawasan Senggarang Kota Tanjungpinang - Tambunan, Friska Flisilia; Rahmawati, Nanik; Arieta, Siti (Peneliti.net, 2023)
Land issues are becoming increasingly complex. The reason is the limited land conditions along with the increasing population, causing land prices to increase rapidly with the changing conditions that occur. In reality, land disputes are generally land between individuals, legal entities or institutions that have socio-political influence and the causes of land disputes are very diverse, usually the reason is unclear land certification procedures, negligence in land management itself, so that it leads to a conflict. This research aims to know and understand the Conflict of Plot Land Disputes in the Senggarang area of Tanjungpinang City. This research uses a qualitative approach. Data collection techniques in this study used observation, documentation and interviews using Snowball Sampling techniques in accordance with predetermined informants. This research uses Lewis Coser's Conflict theory which focuses on the causes of conflict and forms of conflict. In the land dispute that occurred in the Senggarang area, there was land ownership which was claimed by two parties with the same land location, the easy transfer of land rights, especially the sale and purchase of land lots, indicating the lack of knowledge of the local community and the absence of supervision by the government regarding the transfer of land to other parties. The conclusion in this research is that there are indications of land dispute conflicts. keywords : plot land, dispute, community